Mechanism of Vasorelaxation Induced by Coptosapelta flavescens Stems Extract in Rat Thoraric Aorta - Sjarif Ismail; Khemasili Kosala; Ika Fikriah; Agustina Rahayu Magdaleni (Journal of Tropical Pharmacy and Chemistry, 2017)
Coptosapelta flavescens Korth. is a liana plant from the Rubiaceae family. In East Kalimantan, it is also known as â€œAkar Tambolekarâ€ or â€œMerungâ€, it is called â€œakarâ€ or root as its trunk spreads like a root. The plantâ€™s stems are used by ethnic Dayak in East Kalimantan to overcome high blood pressure and it has been proven to induce vasorelaxation on blood vessels, but the its action mechanism in the endothelial or vascular smooth muscle cells (VSMC) are unknown. Vasorelaxation on the blood vessels could be mediated by endothelial or by the VSMC. This research aims to study in vitro which of them is the mechanism of action of Coptosapelta flavescens Stems (CFS) extract. CFS were taken from the secondary forest in Paser Regency, East Kalimantan Province. Its simplicia were macerated with methanol solvent for three days and twice repeated. Vasorelaxation activity of the blood vessels was tested with ratsâ€™ isolated thoracic aorta with endothelial and with the endothelial removed (endothelium-denuded). Both aorta of 3 mm length were soaked into Krebs-Henselheit solution at 37Â°C, pH 7.4 and aerated with carbogen gas. After they have acclimatized, both aortas were contracted with phenylephrine solution, after reaching peak contraction and plateau, the solution of extract or its solvent (Control) was administered in cumulatively increasing doses. The results show that CFS extracts induce vasorelaxation both in the endothelial-intact aorta and in the endothelial-denuded aorta. At high concentrations, the vasorelaxation activity in the endothelial-intact aorta was weaker than that on endothelial-denuded aorta. This study proves that action mechanism of blood vesselsâ€™ vasorelaxation induced by the methanol extract of CFS were more dominantly mediated by the blood vessels smooth muscle; and at high concentrations the endothelial actually weakened the VSMC vasorelaxation activity. Further study is necessary on the mechanism of action vasorelaxation through the modulation of intracellular or extracellular calcium ion channels of VSMC Keywords: Coptosapelta flavescens, vasorelaxation, extract, aorta, in vitro